Relação entre a divulgação de informações por segmentos e a acurácia das previsões de lucros - Souza, Júlia Alves e (2019)
This study aimed to investigate the existence of a relationship between the segment reporting level of Brazilian companies and the accuracy of profit forecasts made by investment analysts. The survey sample comprised 94 companies listed in B3 - Brazil, Bolsa, Balcão. We analyzed segment information for the years 2010 to 2016 and the earnings per share (EPS) forecasts for the years 2011 to 2017. These fo recasts were carried out by the investment analysts and correspond to the companies studied. We subdivided the data analysis into four stages. In the first of these, we applied a checklist and a content analysis of the notes to the financial statements, in order to identify the segment information items disclosed by the companies. In the second stage, we developed the measurement of segment disclosure levels and assigned the scores to the different companies, based on the Item Response Theory. Afterward, in the third stage, we calculated the indicator to represent the accuracy of the profit forecasts made by the investment analysts. We based this indicator on the data regarding the consensus of the forecasts of EPS and the actual values of EPS obtained by the companies. Finally, in the fourth stage, we investigated the relationship between the segment reporting level and the accuracy of profit forecasts, through the application of linear regression modeling for panel data. The results showed that the segment reporting levels varied among the companies since there is discretion for managers to define strategies for presenting the information. We identified three central characteristics of the segment reporting made by the sample companies, which may limit the usefulness of segment information to profit forecasts: i) lack of disclosure items in many companies; (ii) low levels of information disaggregation; and iii) lack of comparability between disclosures made by different companies. The results also showed that the segment reporting level of Brazilian companies is not related to the accuracy of the profit forecasts made by investment analysts. Therefore, profit forecasts were no longer accurate for companies with the highest levels of disclosure. The evidence of the research reinforces the argument that the characteristics of the segment reporting carried out by the companies bring limitations to the usefulness of the reported information and that higher reporting levels do not generate an improvement in the accuracy of the profit forecasts.